Differentiated strategies for digital innovation on television: Traditional channels vs. new entrants - Ranaivoson,Heritiana (2013)
Digitization has greatly influenced the functioning of the television industry. This paper analyzes in particular how French television channels have innovated and adapted to digital technologies. We begin with a typology of innovation in the media by drawing a distinction between product innovations and process innovations, as well as between companies according to whether they were the first to adopt an innovation, or only adopted it once it was already well established in the field. A total of 21 criteria for innovation are analyzed for each of the 15 TV channels in our sample. This paper shows that TV channels have varied innovation strategies. Rather than some channels being innovators on all criteria and others being followers on all criteria, we show that channels adopt, more or less rapidly, certain types of innovation according to the channels characteristics. The characteristics that play the greatest role are the age of the channel, whether it is public or private, and whether it is general or thematic.